ECOPRINT COLOR FASTNESS RESISTANCE ON GOATSKIN MEDIA AGAINST WET RUB AND SUNLIGHT - Nurul Aini; Endang Prahastuti; Mayang Fatkhi Rohmah (E-Journal of Cultural Studies, 2022)
Many artisans prefer to use artificial (synthetic) dyes because they are faster and easier. However, chemical substances from synthetic dye waste are harmful to the environment. Eco-print technique minimizes environmental losses due to natural coloring techniques on printing or transferring colors and motifs from plants directly to the medium. This study aimed to determine the color fastness of eco-print on goatskin material against wet rubbing and sunlight using mordant and tunjung. This research was descriptive research with a quantitative approach. The results showed that the average evaluation value of color fastness to sunlight was 4.75, better than wet rubbing, which got an average evaluation value of 4.42. The bivariate analysis showed the value of sig. (0.043) or H0 was rejected. In conclusion, there was a difference in color fastness from eco-print on goatskin material against wet rubbing and sunlight. Keywords: eco-print, fastness resistance, goatskin.